Cyberbullying and internet gaming disorder in Chinese youth: The role of positive youth development attributes - Xiang, Guo-Xing; Zhang, Yan-Hong; Gan, Xiong; Qin, Ke-Nan; Zhou, Ya-Ning; Li, Min; Jin, Xin (Frontiers in Public Health, 2022)
Introduction As digital natives, young people enjoy the convenience and benefits of the internet but also suffer from unique developmental problems of this age, such as cyberbullying and internet gaming disorder (IGD). Research suggests that these online problem behaviors enjoy high prevalence and various negative impacts. To prevent or intervene, this study attempts to explore the association between cyberbullying and IGD and the potential protectors from the positive youth development (PYD) perspective. Methods Through the convenience sampling method, a sample of 463 Chinese adolescents was recruited and participated in the survey. They completed a questionnaire regarding PYD attributes, cyberbullying, IGD, and demographic information. Results After controlling adolescents' sex and age, results of regression analyses indicated that cyberbullying was positively associated with IGD; PYD attributes had negative cumulative effects on cyberbullying and IGD; and cyberbullying and IGD were negatively related to PYD attributes. Moreover, the mediating effect of PYD attributes was significant in the relationship between cyberbullying and IGD. Discussion Specifically, it is very possible for adolescents who have experienced one online problem behavior to suffer from another one. Fortunately, positive personal attributes could effectively buffer this cascading effect. These findings may provide theoretical and practical guidance for practitioners that improving PYD attributes may be a promising approach to prevent or reduce adolescent cyberbullying and IGD.